Gestión administrativa y su incidencia en el talento humano de la empresa pública vial provincial de Los Ríos, año 2023 - Erazo Anchundia, Vicente Javier (2025)
The present investigation originates in the optimization of resources and the growth of personnel, being the essential elements for the success of the company in the study Administrative management and its impact on the human talent of the Provincial Public Road Company of Los Ríos, year 2023. originates the need to examine how the effectiveness of administrative procedures directly influences the entity, a problem has been detected in the absence of effective human capital management tactics. The general objective is the impact of administrative management on the development and performance of human talent in the Los Ríos Provincial Public Road Company during the year 2023, to detect areas of improvement to suggest strategies, through methodologies with a quantitative approach with descriptive design and correlational, the survey method was used with 56 company employees. A correlation coefficient was carried out to obtain the connection between administrative management and human talent. The negative impact on employee performance was detected due to the absence of constant training and lack of recognition strategies. For this reason, it is essential to promote the administration of policies that strengthen human potential to guarantee the effectiveness and success of the company. The study contributes to the literature of public management and human talent with a basis for subsequent studies in public administration.